SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN DONATUR TETAP MENGGUNAKAN METODE WEIGHTED PRODUCT BERBASIS WEBSITE PADA PANTI ASUHAN AT-TOHIR GODONG - Rahmawati , Putri; Zein Vitadiar , Tanhella; Widoyoningrum , Sri (Inovate, 2024)
At present the use of technology is developing rapidly from various field including within the organitation, but for now the use of information system technology is still not very reaching within Social Welfare Institutions (LKSA) such asa on agency, namely the At-Tohir Godong Orphange. In helping people make donations, they stil use the old and ususal method to determine donors who often come to make donations, namely by simple calculations that use calculations recapitulated fom guestbook written by donors. So in this case the orphange needs a decision-making system to detemine donors who frequently donate, with this it can help the orphange to find out which donors make regular donations, so that it can help the orphange to remind donors to donate again. To deal with the problem, it can be solved by using the weighted product method whis uses multiplication to relate attribute values in the WP method. In this case, the score of each attribute must beraised to the first power of the attribute’s weght. The results of clculation using the weighted product method using 30 samples with the criteria for the typr of work, the number of donations, the time interval for donating, and the accuray in donating has rangking results taken with the final value determined by the sum of each criterion multiplied by the criterion weight. The result with the highest score determines the final value of the rangking. Keywords: donation, donor, weighted product, LKSA.